Shaping Public Discourse: The Role of Editorial Cartoons in Agenda-Setting in Kenyan Newspapers - Okemwa, Titus Ondieki; Njoroge, Wambui; Wabwire, Jonai (Journal of Media and Communication (JMC), 2025)
The purpose of this article is to analyse the role of editorial cartoons in agenda setting within Kenya's two major mainstream newspapers, the Daily Nation and The Standard, over six months. Despite their humorous appearance, editorial cartoons are often overlooked as a significant form of communication that reflects and critiques socio-economic and political issues. This study employed content analysis, which is categorisation of cartoons and captions; headlines and their contents; and semiotic analysis, which involves image analysis, text, and language analysis, to examine 275 editorial cartoons, sorting them thematically to align with the objective of understanding their agenda-setting function. The newspapers were selected due to their dominant circulation, consistent publication, and accessibility in Kenya's print media landscape, with the agenda-setting theory guiding the theoretical framework. Data were summarised using tables, graphs, charts, and percentages. Findings revealed that editorial cartoons predominantly depicted political issues (56%), followed by social (25.09%) and economic themes (18.91%), effectively documenting and critiquing societal problems to influence public discourse. The study concludes that editorial cartoons play a significant role in agenda setting by shaping public perceptions of current events, though some cartoons' complexity necessitates cutlines for clarity. Recommendations include establishing a self-regulatory body for cartoonists and organising symposiums to enhance public understanding of editorial cartoons. This study underscores the importance of editorial cartoons as a powerful communication tool in Kenyan newspapers, contributing to the discourse on visual media's role in reflecting socio-economic and political realities and advocating for further research into African cartooning.